A high-altitude peatland record of environmental changes in the NW Argentine Andes (24 ° S) over the last 2100 years - Schittek, Karsten (2016)
High-altitude cushion peatlands are versatile archives for high-resolution palaeoenvironmental studies, due to their high accumulation rates, range of proxies, and sensitivity to climatic and/or human-induced changes. Especially within the Central Andes, the knowledge about climate conditions during the Holocene is limited. In this study, we present the environmental and climatic history for the last 2100 years of Cerro Tuzgle peatland (CTP), located in the dry Puna of NW Argentina, based on a multi-proxy approach. X-ray fluorescence (XRF), stable isotope and element content analyses (δ13C, δ15N, TN and TOC) were conducted to analyse the inorganic geochemistry throughout the sequence, revealing changes in the peatlands' past redox conditions. Pollen assemblages give an insight into substantial environmental changes on a regional scale. The palaeoclimate varied significantly during the last 2100 years. The results reflect prominent late Holocene climate anomalies and provide evidence that in situ moisture changes were coupled to the migration of the Intertropical Convergence Zone (ITCZ). A period of sustained dry conditions prevailed from around 150 BC to around AD 150. A more humid phase dominated between AD 200 and AD 550. Afterwards, the climate was characterised by changes between drier and wetter conditions, with droughts at around AD 650-800 and AD 1000-1100. Volcanic forcing at the beginning of the 19th century (1815 Tambora eruption) seems to have had an impact on climatic settings in the Central Andes. In the past, the peatland recovered from climatic perturbations. Today, CTP is heavily degraded by human interventions, and the peat deposit is becoming increasingly susceptible to erosion and incision.